REDEFINITION OF FAMOUS BRAND RELATED TO THE APPLICATION OF TRADEMARK LAW BASED ON THE PRINCIPLE OF LEGAL CERTAINTY - Handiriono, Raden; Harmono; Irma Maulida; Nur Alma Azizah B; Insan Kamil (Cirebon International Conference on Education and Economics Proceeding, 2024)
The presence of famous brands has become an inevitable phenomenon in modern society. These brands are not only a part of everyday life, but also play an important role in shaping the social and economic identity of individuals. Therefore, it does not rule out the possibility of infringement in the form of imitation and misappropriation so that it can harm the legitimate owners of well-known trademarks whose existence has not been clearly regulated in the legislation. This research aims to analyse the qualifications of famous brands and evaluate the effectiveness of the existing legal mechanisms in the Trademark Law to implement the principle of legal certainty for famous brands owners. This research examines the criteria used to determine the status of famous brands, including the level of public recognition, length of use, promotion, and market coverage. In addition, this research evaluates how the principle of legal certainty is applied in the enforcement of famous brands rights, as well as the challenges faced in legal practice. Through a normative approach that refers to the application of legislation, literature study, reviewing literature and theoretical studies of legal experts, this study found that although there are laws governing trademarks, there are some things that have not been clearly regulated in it and also the implementation in the field often faces obstacles such as lack of understanding among law enforcement officials and differences in interpretation by the courts. The results of this study are expected to contribute to the development of policies and regulations that are more effective in protecting well-known trademarks in Indonesia, as well as strengthening the principle of legal certainty in the trademark protection system.